Management of content development and subject engagement through an arts matrix model: A case study - Hoeve, Casey D.; Urton, Ellen R.; Bell, Thomas W. (My University, 2014)
From 2007 - 2009, Kansas State University Libraries (K-State Libraries) committed to strategically assess and redevelop their organizational structure. The Libraries’ Strategic Plan and position redistributions commenced in 2007 and 2009 respectively, with adjustments in 2010 to accommodate the university’s “K-State 2025” Strategic Plan. Together, these plans changed the roles of former subject librarians, dividing and transferring responsibilities for outreach, reference, instruction, and collection development. Among the more significant changes was the creation of departments devoted to patron groups, rather than specific academic disciplines. Illustrating how the reorganization changed the roles of traditional library services, this chapter will outline the responsibilities of three librarian positions: Undergraduate and Community Services, Faculty and Graduate Services, and Content (collection) Development. The librarians are also founding members of the K-State Libraries Arts Matrix, an ad hoc team operating within the new organization to enhance communication and expand subject expertise in the visual and performing arts. These transitions presented both opportunities for engagement and specialization, and challenges to communication and subject identity. These issues are addressed, including solutions offered by the matrix model. Although this study is limited by the neoteric existence of this model, and lack of precedents for comparison, K-State Libraries’ example may offer a viable model for institutions adapting to fiscal realities. Additionally, matrices may supplement the traditional subject librarian model for those seeking to enhance engagement and collaboration. This chapter offers further insight into a strategic planning process, as well as a transparent, inclusive strategy for librarians adjusting to organizational change.
Keywords: Collection development; Matrix; Reorganization; Engagement; Team-based